Reduced right ventricular diameter during cardiac arrest caused by tension pneumothorax – a porcine ultrasound study. Issue 7 (28th May 2017) - Caap, P.; Aagaard, R.; Sloth, E.; Løfgren, B.; Granfeldt, A.
Abstract : Introduction: Advanced life support (ALS) guidelines recommend ultrasound to identify reversible causes of cardiac arrest. Right ventricular (RV) dilatation during cardiac arrest is commonly interpreted as a sign of pulmonary embolism. The RV is thus a focus of clinical ultrasound examination. Importantly, in animal studies ventricular fibrillation and hypoxia results in RV dilatation. Tension pneumothorax (tPTX) is another reversible cause of cardiac arrest, however, the impact on RV diameter remains unknown. Aim: To investigate RV diameter evaluated by ultrasound in cardiac arrest caused by tPTX or hypoxia. Methods: Pigs were randomized to cardiac arrest by either tPTX ( n = 9) or hypoxia ( n = 9) and subsequently resuscitated. Tension pneumothorax was induced by injection of air into the pleural cavity. Hypoxia was induced by reducing tidal volume. Ultrasound images of the RV were obtained throughout the study. Tension pneumothorax was decompressed after the seventh rhythm analysis. The primary endpoint was RV diameter after the third rhythm analysis. Results: At cardiac arrest the RV diameter was 17 mm (95% CI: 13; 21) in the tPTX group and 36 mm (95% CI: 33; 40) in the hypoxia group ( P < 0.01, n = 9 for both). At third rhythm analysis RV diameter was smaller in the tPTX group: 12 mm (95% CI: 7; 16) vs. hypoxia group: 28 mm (25; 32) ( P < 0.01). After decompression no difference existed between groups: tPTX 29 mm (95% CI: 23; 34) vs. hypoxia 29 mm (95% CI: 20; 38). Conclusion: The RV diameter is smaller during cardiopulmonary resuscitation in cardiac arrest caused by tPTX when compared with hypoxia. The difference disappears after tPTX decompression.